Eco-friendly microwave assisted sustainable coloration of silk and wool fabric with Acid Blue 07 dye - ÖZOMAY, MERAL (My University, 2023)
Environment-friendly textile processing is the demand of the current global scenario, where the application of sustainable technologies such as microwave radiation has been gaining fame in all global fields due to their green and human-friendly nature. This study has been conducted to employ sustainable technology such as microwave (MW) rays for dyeing polyamide-based proteinous fabric using Acid Blue 07 dye. The fabric before and after MW treatment for up to 10 min has been dyed using an acid dye solution. Spectrophotometric analysis of the dye solution was performed before and after irradiation at a specific selected level. Using selected dyes and irradiation conditions, a series of 32 experiments using a central composite design has been employed. The shades made at selected conditions of irradiation and dyeing were assessed for colorfastness as per ISO standards. It was observed that for dyeing silk, 55 mL of Acid Blue 07 dye solution containing 1 g/100 mL salt solution at 65 °C for 55 min should be employed after MW treatment for 10 min. In comparison, for dyeing wool, 55 mL of Acid Blue 07 dye solution containing 2 g/100 mL salt solution at 65 °C for 55 min should be employed after MW treatment for 10 min. Physiochemical analysis shows that sustainable tool has not altered the chemical nature of fabric but has modified the fabric surface physically to enhance uptake ability. Colorfastness shows that the shades made have offered good resistance to fade and have given good to excellent ratings on the gray scale.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Health Sciences; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Yaşam Bilimleri (LIFE); Mühendislik; Farmakoloji ve Toksikoloji; MÜHENDİSLİK, ÇEVRE; TOKSİKOLOJİ; Engineering, Computing & Technology (ENG); Life Sciences (LIFE); ENGINEERING; PHARMACOLOGY & TOXICOLOGY; ENGINEERING, ENVIRONMENTAL; TOXICOLOGY; Çevre Kimyası; Fizik Bilimleri; Kirlilik; Sağlık, Toksikoloji ve Mutajenez; Environmental Chemistry; Physical Sciences; Pollution; Health, Toxicology and Mutagenesis; Colorfastness; MW radiation; Silk; Sustainability; Textile effluent; Wool